Об определении граничной функции для уравнения колебаний прямоугольной мембраны - Насибзаде, В.Н. (Проблемы управления и информатики, 2017)
Розглянуто задачу визначення граничної функції для рівняння коливань прямокутної мембрани. Пошук невідомої граничної функції зводиться до задачі мінімізації функціонала, побудованого за допомогою додаткової інформації, отримано градієнт функціонала, необхідні і достатні умови оптимальності. Наведено алгоритм пошуку оптимального керування методом проекції градієнта. The problem of determining the edge function, for equation of rectangular membrane librations is considered. The search for unknown edge function is reduced to the problem of functional minimization, constructed by means of additional information the gradient of a functional is obtained, the necessary and sufficient optimality condition is derived. The search algorithm of optimal control, by the method of gradient projections is presented.